SEMIOTIC ANALYSIS OF TYPOGRAPHY IN APPLE VIRTUAL ADVERTISEMENT - Yuda Suryasa Sjaerodji; Desi Indrawati (Lire Journal (Journal of Linguistics and Literature), 2022)
Nowadays, the format of digital technology allows advertisers to include virtual advertisements such as brand names and logos into YouTube channels. Additionally, those parts have become a marketing strategy technique through advertising. This research aims to analyze the semiotic typography components of Apple's virtual advertisement on YouTube and to find out the meanings constructed on Apple's virtual advertisement. This research was conducted qualitatively to analyze the semiotic typography components and the meanings constructed in Apple's virtual advertisement on YouTube Apple Channel, Introducing iPad Air — Apple in 2020. In doing so, this research deals with the semiotic analysis of typography suggested by Van Leeuwen (2006). The results of this research show that there were two elements inside, they were verbal and nonverbal signs. According to the elements, those signs may appear in the form of verbal and nonverbal, such as music, sound effect, typeface, anatomy of letters, font size, shape, color, motion (kinetic typography), model, and situation. In addition, those components were proven to have certain meanings that qualify the insight of Apple virtual advertisement depending on the nature of their elements.